THE APPLICATION OF THE LEARNING STRATEGY TO IMPROVE THE SPEAKING SKILL OF THE SECOND GRADE STUDENTS AT SMA UII YOGYAKARTA IN THE ACADEMIC YEAR 2011/2012 - Permana, Dira (IKIP Mataram, 2014)
The objectives of this study were to identify the problems of the second grade students in speaking English and to discover the effective steps of the learning strategy to improve the speaking skill of the second grade students at SMA UII in the academic year 2011/2012. This study applied a classroom action research and was conducted in two cycles consisting of planning, acting, observing, evaluating, and reflecting. Subjects of the research were the second grade students of SMA UII in the academic year 2011/2012. Data collecting techniques used were observation, interview, diary and speaking test. Data analysis techniques used were descriptive analysis. Based on the research, there were four strategies applied in cycle I, i.e., the strategies of asking for clarification or verification, grouping, repeating and placing new words into a context. The result of strategies application in cycle I gave positive and negative responses that it did not give much significance to the students? speaking skill. The highest speaking score of the students in cycle I was 18. Therefore, revision was done. There were two strategies that must be revised in cycle II, which were the strategies of grouping and repeating. As the revision was done in cycle II, students showed positive response and gave significant improvement to the students? speaking skill. The highest speaking score of the students in cycle II was 27. Thus, it can be concluded that the learning strategy is successfully implemented and improves the speaking skill of the second grade students at SMA UII in the academic year 2011/2012.